What Change Can The New Developments In Energy Sector Bring Into the World`s Energypolitical and Geopolitical Order? - TUTULMAZ, Onur (Journal of Economic Development, Environment and People, 2014)
The recent developments bring US to a leading natural gas and oil producer position. The attempts in last 20 years to bring new horizontal drilling and hydraulic fracturing technologies together have developed a success in shale gas and oil production in US; the production volumes has reached to a position to redefine the market. Last estimations are bringing more information about the shale capacities of the major basins of the world. However, the estimates are based on a wide range of assumptions and consequently their results vary in a large scale. In any case, these developments have crucial economic, political and geopolitical consequences on the energy market, petroleum producer and consumer countries and regions. Despite the wide range of ambiguity of the estimated size of the resources, the estimations show US and North America has one of the biggest potential, already turning technology into the giant production numbers. Some of the estimations allege so big numbers can even mean to a new world order. The asymmetric nature of the potential, can also be said, increases some of the expected impacts too. In this study, basically, we want to supply an initial solid and economical evaluation to this ambiguity. We are trying to shape a frame for the new energy potential and to put it in a place in the current practice of the world. Secondly, in this context, we are underlying here some of the possible economic and geopolitical consequences each of which can constitute a subject of deeper study.